Psychological and spiritual effects of light and color from Iranian traditional houses on dwellers - Honey Arjmandi; Mazlan Mohd Tahir; Hoda Shabankareh; Mohamad Mahdi Shabani; Fereshteh Mazaheri (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2011)
Light and color are the elements that has been playing important role in traditional architecture of Iran. Application of shadow and light with each other has been from the works that gives the mystical sense to the space, especially in religious spaces such as mosques. In view of light, as a major space component, the overall composition, with adjacent servant spaces, find a particular form of organization, which is centralized and where hierarchies define the general pattern. The order of structure, in which light comes as a containing discovering geometry, commands subsidiary openings, which imposes a disciplined regularity of spaces whilst offering greater complex layers of perception. In Iranian architecture, the study of light and color, in accordance with volumes and structure, has always been considered as an essential part of the different stages of the building and its realization. Giving the sensation of unity, this remains at the center of some conceived world‟s spirituality. Unfortunately false imitations from western architecture have given beautiful features but senseless spaces to the contemporary architecture of Iran. the proper teaching and tutoring the Islamic architecture with its principles, especially with suitable light and color applied, not only can describe a suitable feature of architecture, but also defines it in a word that revives the identity of Iranian architecture.